O uso de células-tronco adiposas e da técnica da tubulização na regeneração do nervo facial em ratos wistar após transecção com perda de substância - Poeta, Josiel Schilling (2018)
Introduction: Lesions affecting the peripheral nerves are quite common and can cause devastating damage to their lives of individuals, leading to important functional changes such as pain, morbidity and disability as well as, affecting their psychological condition. When the VII pair of cranial nerve is affected, patients may develop Peripheral Facial Paralysis (PFP), which include aesthetic, functional and emotional damages, as well as pain and discomfort. Treatment for lesions involving the peripheral nerves still presents limitations, since post-surgical results remain uncertain and unsatisfactory, especially in cases where nerve damage causes loss of substance. The use of autologous nerve grafting remains the "gold standard" of treatment; although it does present some important disadvantages. Trying to overcome all the difficulties and limitations, regenerative medicine together with tissue engineering have united their efforts with the purpose of improving the surgical techniques in the repair of this type of injury. Thus, in this context, many researches are being carried out with the aim of developing bioabsorbable materials associated with neurotrophic factors that can be used by the tubulization technique in substitution of the "gold standard". Objective: To evaluate the regeneration of the facial nerve of wistar rats submitted to a total transection of the nerve with loss of substance through the use of the tubulization technique with a PLGA / PCL polymer and autologous adipose stem cells. Material and Methods: 72 wistar rats were randomly divided into 3 groups (A, B, C) and submitted to a surgical procedure of injury (total transection with loss of substance) in the mandibular branch of the facial nerve, forming a gap of 6 mm. Immediately after the injury, the surgical procedure of nerve repair was performed according to the group to which they belonged. The rats of group A (control) were treated through the autologous nerve graft, with suture in the stumps. Group B rats were treated by the tubulization technique using a PLGA / PCL absorbable polymer sutured between the stents. The rats of group C were also treated by the tubulization technique, with the same polymer, but containing a quantity of autologous adipose stem cells in their interior. After 30, 60 and 90 days, the animals were euthanized for histological analysis. Results: The presence of the PLGA / PCL polymer, used by the tubulization technique, appears to have stimulated the formation of fibrosis in all evaluated groups. In 30 days there was no difference in the regeneration of nerve fibers between the three methods used to treat the facial nerve lesion of the rats used in this experiment. The use of stem cells associated with the PLGA/PCL tube presented better results than the "gold standard" in only 60 days. At 90 days, the "gold standard" and the technique of tubulization, without the use of stem cells, had the same results in nerve regeneration, and still, they were superior in relation to tubulization with the use of stem cells.